Texts Classification and Sustainability: A Case of Facebook Sub Genres - Primrose Hlatshwayo; Lettiah Gumbo (Randwick International of Social Science Journal, 2021)
Facebook is one of the latest genres of internet social networks which have attained widespread popularity, yet its defining characteristics have not been systematically described. It has been labeled by some as a genre of possibilities implying that you can come across, new, interesting, unacceptable and controversial texts on FB. Again, it has been labeled a genre of possibilities since it is dynamic, complex and it uses multiple types of sources. FB has emerged as an effective tool for communicating social ties, keeping family and friends updated on latest issues and events, creating new affiliations and as a stage for political or democratic campaigns. The paper investigated the unique elements inherent in Facebook subgenre. It is an endeavour to understand the defining characteristics of Facebook sub genres. The study identified the most useful criteria for categorizing Facebook texts and also identifying the most typical or unique features of FB genres. The researchers endeavored to answer the question what is it that essentially determines the ‘Facebookness’ of FB genres? ‘The study investigated the defining mechanism and sustainability of FB subgenres and established that the most common subgenres on FB are comments, news links, democratic campaigns, business interactions, comments, groups, religious texts and visuals images. The concept The study made reference to some genre theorists in order to facilitate understanding on the aspect of genre classification and sustainability on FB. The study will assist Facebook users to understand the Facebook genres and contribute to the existing pool of applied linguistics knowledge